Πρόταση κατάρτισης φερέγγυου χαρτοφυλακίου με μεθόδους της ανάλυσης δεδομένων - Καραπιστόλης Δημήτριος Ν.; Κάτος Αναστάσιος Β.; Παπαδημητρίου Γιάννης (SPOUDAI Journal of Economics and Business, 2000)
This article (Proposal for the composition of a solvent portfolio with methods of data analysis) refers to the portfolio construction and selection of shares of firms recorded at a Stock Exchange, using multiple criteria referring to the fundamental analysis. Initially, the firms are categorized into five groups with respect to their authority, acceptability and economic health, by using the analysis of correspondences, the principal component analysis and the analysis of ranks in conjunction with ranking in an ascending hierarchy analysis. The solvent portfolio is obtained by applying the method of discriminant analysis to the results found in all previous analyses. This portfolio includes the firms that have the highest authority, acceptability and economic health. JEL Classification: G10